Factors associated with reporting of sexual assault among college and non-college women. Issue 4 (21st September 2017) - Spohn, Ryan; Bjornsen, Abby; Wright, Emily M.
Abstract : Purpose: The purpose of this paper is to examine factors impacting college and non-college women reporting sexual assault to police. The goal is to increase knowledge regarding differences in the rates of reporting and reasons for reporting across these two groups. Design/methodology/approach: Participants were drawn from a national telephone survey of US women and a sample of US college women. Bivariate and multivariate analyses were conducted to determine factors influencing the reporting of sexual assault to police. Findings: Non-college women were more likely than college women to report to police. Women who perceived their victimization as rape were much more likely to report to the police and women who had contact with a helping agency were also much more likely to report their assault. Contacting a helping agency is more relevant to non-college women's reporting to police, while considering the assault a rape is more important for college women. Practical implications: The results suggest that significant work is needed to encourage women in college to view sexual assaults as worthy of reporting. Boosting victim awareness and access to services is paramount. Providing education and empowerment to student victims to inform their perceptions about the definition of rape is vital, as women perceiving sexual assault as rape are more likely to report the incident. Originality/value: The research significantly adds to the literature indicating differences in rates of reporting and the factors that impact reporting uniquely for college vs non-college women.